2008
DOI: 10.1021/mp700095p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gastrointestinal Drug Absorption in Cynomolgus Monkeys

Abstract: Possible factors of species differences in gastrointestinal drug absorption between cynomolgus monkeys and humans were examined using several commercial drugs. Oral bioavailability (BA) of acetaminophen, furosemide, and propranolol in cynomolgus monkeys was significantly lower than that in humans. From the pharmacokinetic analysis, these drugs were found to show the low fraction absorbed into portal vein (FaFg), suggesting that the low BA in cynomolgus monkeys was attributed mainly to the gastrointestinal abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…6) showed an outstanding discrepancy between the predicted and observed AUC oral for neratinib when the value of f a ×F G determined in the monkey was used for the prediction. These results were consistent with previous reports that the intestinal availability in vivo in monkeys is much lower than that in rats (Takahashi et al, 2008) and humans (Akabane et al, 2010;Nishimuta et al, 2010) when the substrate undergoes extensive metabolism in NADPH-fortified intestinal microsomes from monkeys (Akabane et al, 2010). These reports suggested that the monkey is not an appropriate species for the prediction of f a ×F G in humans (Takahashi et al, 2008;Akabane et al, 2010;Nishimuta et al, 2011).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…6) showed an outstanding discrepancy between the predicted and observed AUC oral for neratinib when the value of f a ×F G determined in the monkey was used for the prediction. These results were consistent with previous reports that the intestinal availability in vivo in monkeys is much lower than that in rats (Takahashi et al, 2008) and humans (Akabane et al, 2010;Nishimuta et al, 2010) when the substrate undergoes extensive metabolism in NADPH-fortified intestinal microsomes from monkeys (Akabane et al, 2010). These reports suggested that the monkey is not an appropriate species for the prediction of f a ×F G in humans (Takahashi et al, 2008;Akabane et al, 2010;Nishimuta et al, 2011).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…More recently, several reports have stated that the intestinal transit process, namely Fa or Fg, is a major contributor to the low F in cynomolgus monkeys (Sakuda et al, 2006;Takahashi et al, 2008). However, unlike Fh, which can be easily calculated via conventional pharmacokinetic analysis, Fa and Fg are difficult to evaluate separately, particularly in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) In order to assess the permeability of drugs to the intestinal membrane, various in vitro, in situ and in vivo methods have been utilized. 8,9) Recently, in vitro cell culture models with Caco-2 [10][11][12][13] or Madin-Darby canine kidney (MDCK) 14,15) cells have been widely used to measure the membrane permeability of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The blood-to-plasma concentration ratio (R b ) values of the tested drugs were determined in the previous study. 3,4) However, since it was difficult to determine V portal , it was calculated from the (C in ϪC out ) and C abs of antipyrine, having assumed the Fg of antipyrine to be 1, as shown in Eq. 6.…”
Section: Lc/ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation